THE EFFECT OF USING MONOPOLY GAMES TO LEARN ENGLISH VERBS FOR STUDENTS AT SDN 5 PRAYA - Lalu Rahadian Jayakusuma; Boniesta Zulandha Melani; Lalu Jaswadi Putera (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aimed to test the significant impact of using the Monopoly game on students' vocabulary mastery, specifically receptive English verbs, and to analyze student learning interest perceptions regarding the use of this medium at SDN 5 Praya. The method used was a pre-experimental research design with a One-Group Pretest-Posttest design, involving a single experimental class of 20 Grade V A students. The data analysis, which was conducted after confirming the instruments were valid, reliable, and normally distributed, utilized two main techniques: a Paired Samples t-Test and Normalized Gain. The t-Test results showed a statistically significant difference between the Pre-test mean (65.667) and the Post-test mean (83.000), with a highly significant p-value (4.03x10-10). This led to the rejection of the null hypothesis (H0), confirming that the learning treatment significantly improved students’ learning outcomes. Furthermore, the N-Gain test yielded an average score of 0.58 (58.48%), which falls into the Moderate and